Legal Protection For Workers Through Social Security Program - Nura Damayanti Ariningsih; Windy Ratna Yulifa; Aris Prio Agus Santoso (Publikasi Indonesia, 2021)
The no. 11 2020 law on occupational copyright in section 82 verse 1 mentions that the rule of chapter 18 was changed to read as follows: a social security program includes (a) health insurance, (b) occupational safety, (c) retirement security, (e ) a guarantee of death, (e) a guarantee of death, and (f) a bail of death, but in execution, it cannot be fully implemented by the giver of such social security. The study aims to know the form of legal protection for labor through a social security program by 2020's statute 11 on job copyright and knowing how the implementation of the social security program for labor. The study employed an empirical juridical method using primary and secondary data conducted with a random sampling technique. The data obtained is analyzed with qualitative data analysis. From this study came that legal protection contained rights and obligations. The government has published a 2020 statute of no. 11 to create legal protection for the workforce. But in development in the field, there is still a large amount of manpower that has not earned their right to social security, which means that governments have not been able to provide maximum protection to the workforce.